The Guyana national HIV prevention principles, standards and guidelines (The Ministry GeorgetownGY, 2010)
Presents principles, standards and guidelines as an expressions of the determination to establish prevention as the pillar of the national HIV response in Guyana. Aims to prevent the epidemic from spreading further, and to reduce the impact of the epidemic.
Keywords: HIV